2023
DOI: 10.1128/mbio.01064-23
|View full text |Cite
|
Sign up to set email alerts
|

Dual localization of receptor-type adenylate cyclases and cAMP response protein 3 unveils the presence of two putative signaling microdomains in Trypanosoma cruzi

Abstract: Trypanosoma cruzi is the etiologic agent of Chagas disease, a leading cause of disability and premature death in the Americas. This parasite spends its life between a triatomine insect and a mammalian host, transitioning between developmental stages in response to microenvironmental changes. Among the second messengers driving differentiation in T. cruzi , cAMP has been shown to mediate metacyclogenesis and response to osmotic stress, but this signaling pathway remains large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Understanding the role of cAMP in environmental sensing could lead to the development of strategies to interrupt the parasite’s life cycle and control this silent but deadly disease. Our recent work revealed the presence of two putative cAMP microdomains in T. cruzi : the flagellar distal domain and the contractile vacuole complex, compartments specialized in cell adhesion and osmoregulation, respectively ( 4 ). Studies involving cAMP signaling in three different eukaryotic models have strongly influenced the current direction of my research ( 1 , 7 , 8 ).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the role of cAMP in environmental sensing could lead to the development of strategies to interrupt the parasite’s life cycle and control this silent but deadly disease. Our recent work revealed the presence of two putative cAMP microdomains in T. cruzi : the flagellar distal domain and the contractile vacuole complex, compartments specialized in cell adhesion and osmoregulation, respectively ( 4 ). Studies involving cAMP signaling in three different eukaryotic models have strongly influenced the current direction of my research ( 1 , 7 , 8 ).…”
Section: Commentarymentioning
confidence: 99%
“…Altogether, these findings led me to hypothesize that microenvironmental cues could activate T. cruzi ACs in at least two putative cAMP signaling microdomains: the flagellar distal domain and the contractile vacuole complex. Three cAMP signaling components share dual localization in these microdomains: TcAC1, TcAC2, and TcCARP3, and are involved in cell adhesion, metacyclogenesis, and osmoregulation in T. cruzi ( 4 ). But there are still key unanswered questions.…”
Section: Commentarymentioning
confidence: 99%
“…A PDE localized to the CVC could terminate the signal [118]. Recent work on T. cruzi AC1 and AC2 found that they are present at both the flagellar tip and the CVC [119]. When TcAC1 is overexpressed, it increases both attachment and metacyclogenesis, an effect that can be rescued by expression of truncated mutants with altered localization.…”
Section: Attachment-related Signal Transductionmentioning
confidence: 99%
“…When Tc AC1 is overexpressed, it increases both attachment and metacyclogenesis, an effect that can be rescued by expression of truncated mutants with altered localization. These truncations also reduced the parasites’ ability to recover from hyperosmotic stress through regulatory volume decrease [ 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, the basic components of this signaling pathway are well defined, and the expression of these proteins in different microdomains determines spatiotemporal regulation of cAMP signals (Musheshe et al, 2018;Wang et al, 2022). We have recently identified two putative cAMP signaling microdomains in T. cruzi: the flagellar distal domain (flagellar tip) and the contractile vacuole complex (CVC), structures involved in cell adhesion and osmoregulation, respectively (Chiurillo et al, 2023). However, just a few components of this pathway have been characterized in T. cruzi (Lander et al, 2021;Schoijet et al, 2019).…”
mentioning
confidence: 99%